Technical Standards, Intellectual Property, and Competition—A Holistic View - Nuno Pires de Carvalho (Washington University Journal of Law & Policy, 2015)
Until now, most of the literature that regards the interaction between intellectual property and both mandatory and voluntary technical standards has been limited to a particular area of intellectual property. This Article examines the interaction from a holistic perspective, involving the main intellectual property disciplines: patents, trademarks, and copyrights. Most generally, a tension exists between intellectual property and technical standards due to their differing—and somewhat opposing—objectives and public policies. Further, the interaction between technical standards and intellectual property typically depends on the categorization of the technical standard as mandatory or voluntary. Because the public policies that inform technical standards are oriented towards reducing product and service differentiation, they reduce market freedom. The reduction in market freedom is limited, however, because technical standards are frequently adopted for technical and economic efficiency, which may have a downstream, positive effect on competition.
Keywords: Intellectual property; voluntary technical standards; mandatory technical standards; technical standards